MAQASID AL-SHARIAH FOR THE ESTABLISHMENT OF INTERNATIONAL REGIME - Surwandono, Surwandono; Retnoningsih, Tri Astuti Susanthi; Meiliyana, Ade (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2018)
Approach to understand an international organization behavior is rested on the domination of Western structural approaches such as realism, liberalism, and cognitivism. These approaches have inflicted serious problem to have a good grip on the behavior of the international regime in Islam World and Third Countries World. This research was aimed to elaborate the relevance of Islamic approaches in the framework of maqashid shariah for the management of international regime. This framework which leans primarily on the value of “protection” is able to elucidate new insight upon the understanding of international regime reality in Islamic World and Third Countries World. It also becomes a new alternative method to conceive the behavior of international regime and criticizes the Western structural approaches which emphasize the value of “asymmetric” in regard to the international relations.